Conceptual Spatio-Temporal Data Model Design For Plant Biodiversity - Wahid, Mohd. Taib; Kamruzzaman, A. Z. M; Mohamed Shariff, Abdul Rashid; Selamat, Harihodin (2005)
Malaysia has been acclaimed as one of the mega diversity countries in the world also has been ranked the 12th richest country in terms of the number and diversity of plant species. To manage the large amount of plant species of Malaysia has become very essential with rapid growth in the number of plant species due to their rich economic importance. Although the extensive research has been performed in plant biodiversity area recent years, managing plant biodiversity data with database system still poses many challenges. Traditional database systems (built on relational hierarchical and network models) which are widely used for commercial applications such as banking fail to meet the modeling and processing requirements of the biodiversity data. Recently developed BODHI (Biodiversity Object Database arcHItecture) data model which is designed based on Indian plant biodiversity and only support spatial data. Geographical data have an object and location, attribute and time. Integration between plant Biodiversity data (BODHI) and geographical data with event-based approach can make an enhancement for the plant biodiversity data analysis and data manipulation. In addition to this, most of the data models are relational model. However, relational model can not support temporal data (time) effectively; it is only support spatial data (space). Main purpose of this paper is to design a conceptual plant biodiversity data model which is combination of BODHI data model and event-based techniques by using object relational approach to support temporal data. Therefore, conceptual data model by using object relational and event based is an appropriate approach to design a plant biodiversity data model. Moreover, Forest department, land and agricultural management and other related research organization could be benefited from the outcome of this model.